Analisis Good Corporate Governance Terhadap Kinerja Keuangan Perusahaan Perbankan Yang Terdaftar Di BEI - A.A Sagung Anggun Dinda Pratiwi; Ni Luh Kardini; Komang Asri Pratiwi (Otonomi, 2023)
One of the keys to a company's success in facing obstacles and global business competition is principlesGood Corporate Governance. Good Corporate Governance is one of the most important elements in improving economic efficiency efforts which includes a whole series of relationships between company management, board of directors, board of commissioners,stakeholder, and other shareholders. In general, there are many things that influence company performance, both in terms of monitoring by the board of commissioners, monitoring by the audit committee on company performance or company ownership which creates investor confidence in the company. The aim of this research is to analyze the simultaneous and partial influence of board of commissioners, audit committee and managerial ownership variables on the financial performance of banking companies listed on the IDX 2017-2021. The type of data used in this research is quantitative data with the data source being secondary data. Samples were selected using the methodpurposive sampling which was based on certain criteria, 21 companies were selected as samples so that the total data studied was 105 data from 2017-2021. This research technique uses multiple linear regression analysis techniques. Partially, this research states that the independent board of commissioners has a positive and significant effect on financial performance. The audit committee does not have a significant effect on financial performance. Managerial ownership has a positive and significant effect on financial performance. The independent board of commissioners, audit committee and managerial ownership simultaneously have a positive and significant effect on financial performance. In the determination test, it was found that 2.6% of the independent board of commissioners, audit committee and managerial ownership had an influence on financial performance, while 97.4% was influenced by other factors outside the independent variables of this research. Keywords : Independent Board of Commissioners, Audit Committee, Managerial Ownership, Financial Performance